Odpowiedzi

2010-03-07T16:15:23+01:00
A) =6x-24-2=6x-22
b) =2x+2-3x+3=5-x
c) =-3y+6+4y+8=y+14
d) =5x-5y-5-4x-8=x-5y-13
e) =6a+2b-2x
f) =2x-2-2x=-2
2010-03-07T16:17:47+01:00
A) 6(x-4)-2=6x-24-2=6x-26=2(3x-13)
b) 2(x+1)-3(x-1)=2x+2-3x+3=-1x+5=-(x-5)
c) -3(y-2)+4(y+2)=-3y+6+4y+8=y+14
d) 5(x-y-1)-4(x+2)=5x-5y-5-4x-8=x-5y-13
e) 2(3a+b)-2x=6a+2b-2x=2(3a+b-x)
f) 1/2(4x-4)-2x=2x-2-2x=-2
2010-03-07T16:18:26+01:00
A) 6(x-4)-2=6x - 4 - 2 =6x-2
b) 2(x+1)-3(x-1)=2x+2-3x+3=-x+5
c) -3(y-2)+4(y+2)=-3y+6+4y+8=y+14
d) 5(x-y-1)-4(x+2)=5x-5y-5-4x-8=x-5y-13
e) 2(3a+b)-2x=6a+2b-2x
f) 1/2(4x-4)-2x=2x-2-2x=2

mam nadzieje ze pomoglam